STRATEGI DIGITAL MARKETING UMKM MEUBEL ACHI HASSAN DALAM PENINGKATAN HASIL PENJUALAN - Baiq Laila Wulandari; Fatana Suastrini (Nusantara Hasana Journal, 2025)
This research aims to examine the digital marketing strategy implemented by Achi Hassan Meubel UMKM in increasing sales results, as well as identifying the challenges, obstacles and solutions faced in implementing this strategy in Semparu Village, Kopang District, Central Lombok, West Nusa Tenggara. This research uses a qualitative method with a case study approach. Data was collected through observation, interviews and documentation. Data analysis was carried out using thematic analysis techniques. The results of this research show that the digital marketing strategy implemented by Achi Hassan Meubel UMKM, especially through the WhatsApp, Facebook and Tiktok platforms, has had a positive impact on increasing sales and expanding market reach. Achi Hassan Furniture UMKM also face challenges and obstacles in digital marketing strategies such as fraud, competition and building consumer trust. So Achi Hassan furniture implements solutions to face challenges and obstacles through consumer identity verification, digital content differentiation strategies, and transparency of product information.